Fungsi Komisi Penyiaran Indonesia terhadap Pelanggaran Siaran Televisi - Anak Agung Ayu Mas Merta Sari; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
Broadcasting through television media is an effective and efficient way to convey information, education and inspiration to the public or society. The information that is presented must have been packaged in such a way that it is interesting to display. However, in practice, there are frequent violations of television broadcasting, especially violating broadcasting code of conduct and broadcast program standards. For this reason, this study aims to determine the regulation of television broadcasts in Indonesia, and to determine the sanctions for violations of television broadcasting. The research method used is normative research with several problem approaches, namely the conceptual approach and the statutory approach. Sources of legal materials used are primary and secondary legal materials. Based on the research that has been done, it shows that the regulation of television broadcasts carried out by the Indonesian Broadcasting Commission is expected to be able to regulate broadcasts so that they do not deviate from broadcast corridors that are in accordance with sound broadcast standards or categories and are able to provide inspiring information and education to the public watching the broadcast. The imposition of sanctions for stations that violate must also be firmer and have a deterrent effect so that the same incident does not occur again. For this reason, it is better if the government, television stations, and the community must work together to create healthy broadcasts not only based on ratings and material benefits, but must be based on the concept of healthy and inspiring education among the public.